2010
DOI: 10.1186/1471-2458-10-389
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health issues facing Southeast Asian beer promoters: a qualitative pilot study

Abstract: BackgroundIn Southeast Asia, hundreds of thousands of young rural women migrate from their villages to the larger cities in search of work. Many find employment with beer companies or in the clubs where beer is sold, promoting the sale of beer. Previous research suggests these young migrants are in a highly vulnerable position. This paper will describe the findings of an October 2009 meeting to develop a research agenda on the sexual and reproductive health of beer promoters and a subsequent pilot study of foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 3 publications
1
46
0
Order By: Relevance
“…The beer promoters’ health seeking practices were influenced and are similar to those described by beer promoters elsewhere [ 10 ]. health services supply and demand-side barriers.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The beer promoters’ health seeking practices were influenced and are similar to those described by beer promoters elsewhere [ 10 ]. health services supply and demand-side barriers.…”
Section: Discussionsupporting
confidence: 53%
“…Their exact number is not known, but unofficial estimates suggest that there are 8,000 to 10,000 women working in the bars, beer shops and nightclubs, as beer promoters in Vientiane Capital City [ 10 ]. Beer promoters are differentiated from beer sellers and are employed by both international and national breweries to promote the sales of beer in restaurants and other establishments [ 10 ]. They are predominantly young, female and attractive and often required to wear revealing, branded uniforms of the brewery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our pilot study of rural-to-urban migrant beer promoters in Cambodia, Laos, Thailand, and Vietnam, we found that women's access to reproductive health care services in their urban settings were limited by health care provider stigma, cost, and availability of services, in addition to personal factors such as lack of time and shyness to access services. 9 Health care provider stigma was often related to the assumption that beer promoters provide sexual services to their clients; similar populations of women seeking reproductive health care services, such as Lao sex workers, also experience stigmatizing attitudes from health care providers. 10 We undertook a study of access to reproductive health care services for internal migrant women who work as beer promoters in the Southeast Asian capitals of Bangkok, Thailand; Hanoi, Vietnam; Phnom Penh, Cambodia; and Vientiane, Laos.…”
Section: Introductionmentioning
confidence: 99%
“…Informal work is also associated with a higher risk of experiencing mental illnesses [12,14]. Similarly, qualitative studies showed that informal workers tend to have poor working conditions, irregular incomes, difficulty accessing health services and are vulnerable to catastrophic health shocks [15][16][17].…”
Section: Introductionmentioning
confidence: 99%